(untitled) (Revista LIDER, 2020)
Local development is a concept which has been widely researched for years. Nowadays it is used as law for international policy. However, contributions to its definition have been numerous in many scientific fields. This article proposes a review of this concept and a review of the relationships that local development has with the territory, society and sustainable development.